2020
DOI: 10.1017/cem.2020.396
|View full text |Cite
|
Sign up to set email alerts
|

Just the Facts: What are the roles of oxygen escalation and noninvasive ventilation in COVID-19?

Abstract: A 37-year-old female presents with cough, fever, dyspnea, and myalgias for five days after recent contact with a family member with confirmed 2019 coronavirus disease . Her vital signs include T 38.3°C, HR 108, BP 118/ 70 mm Hg, RR 26 breaths per minute, and oxygen saturation 67% on room air. She is not in respiratory distress currently and is protecting her airway. Her chest X-ray reveals bilateral airspace opacities. You plan to immediately intervene and address her hypoxia. KEY CLINICAL QUESTIONS How can ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…However, many patients can be safely and appropriately managed with non-invasive means of oxygenation and ventilation (i.e., interventions other than endotracheal intubation). For patients with hypoxemia, supplemental oxygen via a low-flow system such as nasal cannula can be used initially [ 7 , 29 ]. If oxygen flow rates greater than 6 L/min via nasal cannula are needed to maintain an oxygen saturation ≥ 90–92%, supplementation via a facemask can be utilized for higher flow rates, or a Venturi mask can be utilized [ [6] , [7] , [8] , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many patients can be safely and appropriately managed with non-invasive means of oxygenation and ventilation (i.e., interventions other than endotracheal intubation). For patients with hypoxemia, supplemental oxygen via a low-flow system such as nasal cannula can be used initially [ 7 , 29 ]. If oxygen flow rates greater than 6 L/min via nasal cannula are needed to maintain an oxygen saturation ≥ 90–92%, supplementation via a facemask can be utilized for higher flow rates, or a Venturi mask can be utilized [ [6] , [7] , [8] , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…For patients with hypoxemia, supplemental oxygen via a low-flow system such as nasal cannula can be used initially [ 7 , 29 ]. If oxygen flow rates greater than 6 L/min via nasal cannula are needed to maintain an oxygen saturation ≥ 90–92%, supplementation via a facemask can be utilized for higher flow rates, or a Venturi mask can be utilized [ [6] , [7] , [8] , 29 ]. For patients who remain hypoxic or demonstrate increased work of breathing despite these interventions, HFNC or NIPPV can be utilized [ 6 , 7 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The training focused on the pathophysiology of COVID-19, principles of patient management, and the foundations of high-performance teamwork. We adapted our patient care procedures to de-emphasize bag-mask ventilation in favor of an escalating oxygen therapy regimen [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Due to the peculiar pathophysiology of this disease, it is important to maintain a gradual administration of respiratory support (oxygen escalation) [30]. However, a retrospective study comparing 373 CoViD-19 patients with a similar group admitted to the same hospitals for viral pneumonia between 2013 and 2017, showed that rapid growth in oxygen requirements itself is highly predictive of the need for positive pressures [31].…”
Section: Tablementioning
confidence: 99%